A Career Guidance Software for Selection of College Majors in Universiti Putra Malaysia - Wong, Kok Fye (2006)
Malaysia university candidates are facing indecisiveness in college major selection in their tertiary education; and thus a career guidance tool is needed to assist them in their college majors’ selection. This research was intended to develop a computer assisted career guidance (CACG) software, which consists of a vocational interest inventory (Putra College Majors Inventory) and a college major finder (Putra College Majors Finder). Putra College Majors Inventory (PCMI) is a vocational interest inventory which consisted of 360 items and was developed based on John Holland’s Theory of Vocational. The process of developing PCMI followed the guideline from Brown (1983), which involved specification of instrument purpose, translating purpose into operational term, develop instrument plan, item writing, item analysis, standardization of scoring, and technical analysis of test. Reliability analysis and content validity were performed to ensure the reliability and validity of PCMI. Putra College Majors Finder (PCMF) consisted of a list of 44 Bachelor Degree programmes of Universiti Putra Malaysia (UPM) where individual programme was assigned with a three-letter environment code. PCMF was developed by assessing the undergraduates’ environment in UPM via Environment Assessment Technique (EAT). A total of 2505 second last semester (2004/2005) undergraduates from all bachelor degree programmes in UPM have been purposively sampled as the sample for this study. Statistical analysis on PCMI yielded an Alpha Cronbach of .98 and content validity index of 8.76 on a ten-point scale. The study shows that the environment profile for UPM is Social (S), Investigative (I) and Artistic (A). The SIA environment profile of UPM is in line with the university’s mission to be a leading Centre of Learning and Research, contributing not only towards human advancement and discovery of knowledge but also to the creation of wealth and nation building. A CACG software was then developed based on data collected from this study. Correlation analysis was performed between the calculated result from computerized PCMI versus the paper and pencil PCMI. The Degree of Correlation was r (335) =1.00, p<0.01 proving that there were no difference found between them.